2008
DOI: 10.1590/s0036-36342008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the roles of temperature, precipitation, and enso in dengue re-emergence on the Texas-Mexico border region

Abstract: Objective. The goal of this study was to assess linkages between microclimate and longer-term ENSO-related weather forcing on the week-to-week changes in dengue prevalence in Matamoros, Tamaulipas, Mexico, over a recent decade of dengue observations. Material and Methods. An auto-regressive model to evaluate the role of climatic factors (seasurface temperature) and weather (maximum temperature, minimum temperature, precipitation) on dengue incidence over the period 1995-2005, was developed by conducting time-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
99
1
19

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 42 publications
14
99
1
19
Order By: Relevance
“…Una asociación positiva similar entre el dengue y el régimen de lluvias ha sido evidenciada por Brunkard, et al, (25) en la ciudad de Matamoros en México, pero, a diferencia del presente estudio, en Matamoros el rezago observado en la precipitación fue de dos semanas, mientras que en otro estudio, en Barbados (26), el rezago fue de siete semanas.…”
Section: Discussionunclassified
“…Una asociación positiva similar entre el dengue y el régimen de lluvias ha sido evidenciada por Brunkard, et al, (25) en la ciudad de Matamoros en México, pero, a diferencia del presente estudio, en Matamoros el rezago observado en la precipitación fue de dos semanas, mientras que en otro estudio, en Barbados (26), el rezago fue de siete semanas.…”
Section: Discussionunclassified
“…Warmer temperature increase the frequency of blood feeding and viral development rate, and shortens the EIP (Brunkard et al, 2008;Chan and Johansson, 2012;Watts et al, 1987). These relationships partially drive the observed seasonal pattern of higher incidence during the warm season (Carbajo et al, 2012).…”
Section: Introductionmentioning
confidence: 86%
“…10 Significant efforts have been made to understand the effects of climate variability on the transmission dynamics of DF. Increases in temperature, sea surface temperature, and precipitation and the presence of El Niño events have been associated with elevated DF incidence in Mexico 11,12 and other countries. 8,13,14 Previous studies relating climate variability to DF in Mexico have analyzed time series of DF cases up to 1 year, 11,15,16 and only a few have analyzed series of up to 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…8,13,14 Previous studies relating climate variability to DF in Mexico have analyzed time series of DF cases up to 1 year, 11,15,16 and only a few have analyzed series of up to 10 years. 12,17 Such short series pose problems for disentangling the overall associations between climate variability and DF. Our study analyzes 23 years of reported DF cases to examine associations with temperature, precipitation, and El Niño events.…”
Section: Introductionmentioning
confidence: 99%